Politeness Maxims used on Talkshow Video Entitled ”Culture Shock or Shock Culture, Which ine” in DEDI_4548 Youtube Channel - Andini, Nauriyah; Saehu, Andang; Wardoyo, Cipto (STBA Prayoga Padang, 2025)
This study examines the application of Geoffrey Leech’s politeness principles in the talk show “Culture Shock or Shock Culture, Which One?” to understand how politeness maxims contribute to effective communication. Using a qualitative approach, the dialogue was analyzed based on Leech’s six maxims: tact, generosity, approbation, modesty, agreement, and sympathy. The findings reveal that all maxims are present, with the agreement maxim being the most frequently observed (4 instances), followed by the approbation maxim (3 instances), generosity maxim (2 instances), and tact and modesty maxims (1 instance each). The predominance of the agreement maxim highlights its role in fostering a harmonious conversational environment, avoiding conflict, and encouraging mutual respect. The tact maxim minimizes imposition, while the approbation maxim strengthens rapport by emphasizing praise. Additionally, the modesty maxim promotes humility, and the generosity maxim reflects the speakers’ willingness to prioritize others. These results suggest that politeness maxims are essential in maintaining positive and engaging talk show interactions, with the agreement maxim playing a central role in ensuring smooth and respectful discourse.